Transformation of the technical regulation system in the European Union - Sokolova , Viktoriya (Pressing Problems of Public Administration, 2024)
the article examines the evolution of the technical regulation system in the European Union (EU) and its impact on international trade. The authors analyse the key stages of the development of technical regulation, from the use of Old Approach directives to the introduction of the New Approach and the establishment of the New Legislative Framework. The study focuses on the harmonization of standards, implementation of conformity assessment procedures, strengthening of market surveillance, and minimization of technical barriers to trade. Special attention is paid to the unique model of technical regulation in the EU, which fosters economic integration, ensures a high level of safety and product quality, and supports the competitiveness of goods in international markets. The article highlights the historical aspects of the system’s development, its influence on the formation of the single European market, and its effectiveness in creating a transparent and harmonized regulatory environment. Particular focus is given to the prospects of Ukraine’s integration into the European technical regulation system. The significance of the Agreement on Conformity Assessment and Acceptance of Industrial Products (ACAA) is discussed, as it offers Ukrainian manufacturers access to the EU market without additional certification. This approach will facilitate trade, reduce export costs, enhance product competitiveness, and promote economic cooperation with EU countries. The research methodology is based on historical, systemic, and comparative methods of analysis, ensuring a comprehensive approach to studying the topic. The research logic is built on a chronological review of the development of the EU technical regulation system, which allowed identifying its key stages, transformations, and adaptation to modern challenges. The results of the study highlight the importance of technical regulation as a tool for economic integration and competitiveness, as well as its significance for harmonizing international trade. Recommendations are presented for improving Ukraine’s national technical regulation system based on European experience, particularly by incorporating international standards and requirements.